A Thomas More source book - Wegemer, Gerard, 1950-; Smith, Stephen W., 1950-; More, Thomas, Saint, 1478-1535. (Washington, D.C. : Catholic University of America Press, 2004)
"This source book brings together classic text by and about Thomas More - poet, scholar, statesman, family man, educational reformer, philosopher, historian, and saint. In addition to serving as an introduction to More's life and writings for the general reader, this collection is a helpful companion to the study of More's literary and philosophical masterwork, Utopia, and to the study of sixteenth-century history, literature, philosophy, or politics."--Jacket
Earliest accounts of Thomas More's life -- Writings on love and friendship -- Writings on education -- Writings on government -- Writings on religion -- More's last days.
Includes bibliographical references (pages 375-379) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: More, Thomas, -- Saint, -- 1478-1535.; Henry -- VIII, -- King of England, -- 1491-1547 -- Relations with humanists; Henri -- VIII, -- roi d'Angleterre, -- 1491-1547 -- Et les humanistes; Henry -- VIII, -- King of England, -- 1491-1547; More, Thomas, -- Saint, -- 1478-1535; More, Thomas; More, Thomas, -- Saint, -- 1478-1535.; More, Thomas, -- Saint, -- 1478-1535 -- Sources; Henry -- VIII, -- King of England, -- 1491-1547 -- Relations with humanists; Christian martyrs -- England -- Biography; Statesmen -- Great Britain -- Biography; Humanists -- England -- Biography; Great Britain -- History -- Henry VIII, 1509-1547 -- Biography; Great Britain -- Politics and government -- 1509-1547.; England -- Intellectual life -- 16th century; Martyrs chrétiens -- Angleterre -- Biographies; Hommes d'État -- Grande-Bretagne -- Biographies; Humanistes -- Angleterre -- Biographies; Grande-Bretagne -- Histoire -- 1509-1547 (Henri VIII) -- Biographies; Grande-Bretagne -- Politique et gouvernement -- 1509-1547.; Angleterre -- Vie intellectuelle -- 16e siècle.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- Europe -- Great Britain; Christian martyrs; Humanists; Intellectual life; Politics and government; Relations with humanists; Statesmen; England; Great Britain; Quelle; Christian martyrs -- Great Britain -- Biography; Statesmen -- Great Britain -- Biography; Humanists -- Great Britain -- Biography; Great Britain -- History -- Henry VIII, 1509-1547 -- Biography; Great Britain -- Politics and government -- 1509-1547.; Great Britain -- Politics and government -- 1485-1603.; Great Britain -- Intellectual life -- 16th century; 1500 - 1599; collective biographies; Biographies; History; Biographies; Biographies